‘Meister Eckhart’s heretical orthodoxy: the danger of preaching doctrine’ - Wendlinder, Anastasia Christine (Medieval mystical theology, 2025)
Meister Eckhart has long been considered one of the most controversial mystics in Christian history, even though he has been praised by recent popes and is widely read by contemporary audiences from every major religious tradition. Still, the nature of his orthodoxy to Christian doctrine remains unresolved: did he skirt heresy or remain faithful to the central tenets of Christianity? This paper considers three potential ‘dangers’ Eckhart’s work might pose, related to the authority structure of the Roman Catholic Church, his departure from conventional religious language about the relationship between humanity and the Divine, and whether he led his audiences astray, or closer to their salvation.